3/4(1/2х + 2/3) = 3х + 2 1/4; 3/8х + 1/2 = 3х + 2 1/4; 3/8х - 3х = 2 1/4 - 1/2; - 2 5/8х = 1 5/4 - 2/4; - 21/8х = 1 3/4; - 21/8х = 7/4; х = 7/4 ; (- 21/8); х = 7/4 * (- 8/21); х = - 2/3. ответ: - 2/3.
Пошаговое объяснение:
3/4*(1/2х+2/3)=3х+2 1/4
3/8х+1/2=3х+9/4
3х+4=24х+18
3х-24х=18-4
-21х=14
х=-0.6
3/4(1/2х + 2/3) = 3х + 2 1/4; 3/8х + 1/2 = 3х + 2 1/4; 3/8х - 3х = 2 1/4 - 1/2; - 2 5/8х = 1 5/4 - 2/4; - 21/8х = 1 3/4; - 21/8х = 7/4; х = 7/4 ; (- 21/8); х = 7/4 * (- 8/21); х = - 2/3. ответ: - 2/3.
Пошаговое объяснение:
3/4*(1/2х+2/3)=3х+2 1/4
3/8х+1/2=3х+9/4
3х+4=24х+18
3х-24х=18-4
-21х=14
х=-0.6